2016
DOI: 10.1007/s11355-016-0296-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen leaching from surface soil in a temperate mixed forest subject to intensive deer grazing

Abstract: We aimed to determine the grazing impact on soil nitrogen (N) mineralization and N leaching in a temperate mixed forest on Mt. Ohdaigahara, central Japan, where Sika deer (Cervus nippon Temminck; hereafter deer) grazing has decreased biomass of Sasa nipponica Makino et Shibata (hereafter sasa) that dominates the forest understory. Soil N mineralization and N leaching of the top 0.3-m layer were measured in situ from 2006 to 2007 by an ion-exchange resin core method inside and outside a deer exclosure. Deer gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In particular, tea and bamboo plantation systems usually receive high levels of nitrogen (N) fertilizer (range from 450 to 1200 kg N per hectare) to increase tea production [6][7]. The amount of N lost via leaching, runoff and nitrificationdenitrification and methods to effectively mitigate these losses have been well documented [8][9][10][11]. Recent studies have indicated that ammonia (NH3) emissions have been increasing over the last few decades on a global scale [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, tea and bamboo plantation systems usually receive high levels of nitrogen (N) fertilizer (range from 450 to 1200 kg N per hectare) to increase tea production [6][7]. The amount of N lost via leaching, runoff and nitrificationdenitrification and methods to effectively mitigate these losses have been well documented [8][9][10][11]. Recent studies have indicated that ammonia (NH3) emissions have been increasing over the last few decades on a global scale [12].…”
Section: Introductionmentioning
confidence: 99%